1975
DOI: 10.1021/jf60200a033
|View full text |Cite
|
Sign up to set email alerts
|

Environmental degradation of the insect growth regulator methoprene. VIII. Bovine metabolism to natural products in milk and blood

Abstract: Methoprene was extensively metabolized by a lactating dairy cow to acetate which was isolated from blood as randomly labeled acetic acid. Radioactive acetate incorporated into milk fat which was degraded to radiolabeled saturated, monoenoic, and dienoic fatty acids. Also isolated from milk were radioactive lactose, lactalbumin, and casein. The presence of [14C]cholesterol (free and esterified) was confirmed in blood, in agreement with a previous study in a steer.Methoprene (1, isopropyl (2E,4£')-ll-methoxy-3,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The extracted lipid (70 mg) was saponified (1 KOH in ~90% ethanol, 75 °C, 1 h), esterified with diazomethane, and purified by TLC (two 20 X 20 cm plates, 1 mm silica 0021-8561/78/1426-0064$01.00/0 © 1978 American Chemical Society gel GF). When the fatty acid methyl ester zone was further purified by TLC on silver nitrate impregnated silica gel plates (Quistad et al, 1975), the radioactivity migrated with saturated fatty acid methyl esters.…”
mentioning
confidence: 99%
“…The extracted lipid (70 mg) was saponified (1 KOH in ~90% ethanol, 75 °C, 1 h), esterified with diazomethane, and purified by TLC (two 20 X 20 cm plates, 1 mm silica 0021-8561/78/1426-0064$01.00/0 © 1978 American Chemical Society gel GF). When the fatty acid methyl ester zone was further purified by TLC on silver nitrate impregnated silica gel plates (Quistad et al, 1975), the radioactivity migrated with saturated fatty acid methyl esters.…”
mentioning
confidence: 99%
“…When methoprene-5-14C was given to cattle, demethylated and deisopropylated metabolites of methoprene were identified in feces and urine (Chamberlain et al, 1975), but radioactivity was associated with milk fat, lactose, lactalbumin, and casein (Quistad et al, 1975c). Methoprene can be partly metabolized to acetic acid by cattle (Quistad et al, 1974), and some of this acetic acid may be used for synthesis of cholesterol (Quistad et al, 1975a).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of methoprene metabolism in a lactating dairy cow (30) given a large single oral dose (465 mg) showed no detectable primary metabolites (< 0.01 ppm) in milk, although 8% of the radioactivity appeared in milk. Since only 1% of this milk radioactivity was present in the trace of methoprene (0.015 ppm) an extensive analysis of the milk was completed (30) and revealed the now familiar array of radiolabeled natural products.…”
Section: Environmental Chemistry and Metabolismmentioning
confidence: 97%
“…A comprehensive study of the environmental fate of methoprene has been completed and reported in detail (23)(24)(25)(26)(27)(28)(29)(30)(31). Perhaps mainly as a consequence of the aquatic use pattern in the control of mosquito larvae, where many nontarget plants and organisms are also exposed, these studies have been unusually broad in scope.…”
Section: Environmental Chemistry and Metabolismmentioning
confidence: 99%